Kecenderungan Bunuh Diri Siswi SMP Korban Perundungan: Sebuah Studi Naratif - Liem, Yani Mulia; Devi, Inez Lyvia; Lailani, Raeda Nur (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2024)
Bullying is a serious problem in education. The number of bullying cases in Indonesia demands that the government, academics, and the wider community pay more attention to this problem. This study aims to further explore the suicidal tendencies of a junior high school student who is a victim of bullying. This qualitative research uses a narrative approach. The participant is a 15 years-old teenager, who is a student of a private junior high school in Sleman Regency, who has been bullied from kindergarten to junior high school. Thematic analysis was conducted to analyze the result. The results showed that long-term bullying can lead to a tendency to self-harm and suicide. Some of the risk factors identified from this study were family members’ inability to understand the victim's condition, poor family's economic condition, neglect of teachers and school friends, and the victim's own capabilities such as communication and emotion regulation skills. This study also identified several protective factors such as family support, teachers and school friends, the victim’s ability to show her feelings, attitude, and behavior.